Seroprevalence of transfusion transmissible infections among blood donors in tertiary care centre of GandhiNagar, Gujarat, India - Dr. Renu I. Sharma; Dr. Kanaiyalal J. Patel; Dr. Harshid Patel; Dr. Chetankumar M. Dharaiya (Tropical Journal of Pathology and Microbiology, 2018)
Background:Transfusion transmissible infections (TTI) is a major challenge to the blood transfusion service all over the world. TTI create a significant burden on health care system that continue to be a threat to safe transfusion practices. Safety of blood is a major concern in transfusion therapy. In spite of advancement of technologies and meticulous testing one cannot detect the infections in “Window Phase”.Aims andObjectives:To study the sero-prevalence of TTIs among blood donors andto assess the trend of TTIsamong blood donors from records at the blood bank of our tertiary care hospital.Materials and Methods: The present study was carried out at Blood bank of GMERS Medical College, Gandhinagar, Gujarat, India and includes the analysis of seroprevalence of HIV, HBV, HCV, Syphilis and Malaria in the blood donors during the period of 3 years and 6 months from January 2015 to June 2018.Results: Out of total 13724 blood donors, replacement donors (52.4%) were more in comparison to voluntary donors (47.6%). The seropositivity among the blood donors in our study was 0.29% for HBV, 0.04% for syphilis, 0.03% for HIV and 0.0% for both HCV and malaria. The seroprevalence of HIV and syphilis showed a declining trend while seroprevalence for HBV was increasing trend over 3 years.Conclusion: Voluntary blood donation, increasing awareness about blood donation in general population, selection of repeat, non- remunerated, regular voluntary blood donors and diligent donor selection are most important to increase blood safety and avoid transmission of infectious disease through blood transfusion.